Staphylococcus schleiferi subspecies coagulans septic shock in an immunocompetent male following canine otitis externa - Andrew D. K. Nguyen; Deborah Moran; Carole-Lynn Eland; Kathryn Wilks (Turkish Journal of Emergency Medicine)
Staphylococcus schleiferi bacteremia is an underappreciated cause of septic shock in the critical care department. Although nominally a coagulase variable Staphylococcus and associated with otitis externa infections in canine species, it has been associated with the metastatic infection including osteomyelitis, endocarditis, nephritis, and meningitis in humans. This report records a possible zoonotic case of S. schleiferi subspecies coagulans bacteremia following canine otitis externa associated with septic shock and endovascular infection precipitating intensive care admission for vasopressor support in an immunocompetent male.